Profesionalisme Manajemen Kerja Perspektif Tafsir Maudhū‘ī: Studi Kasus Oriental Circus Indonesia di Taman Safari - Nurul Hamidah; Mohammad Arif; Ahmad Syaifullah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
This study aims to examine the principles of professionalism in work management within Islam through a tafsīr maudhū‘ī (thematic exegesis) approach to relevant Qur’anic verses, and to analyze their relevance to management and labor practices at Oriental Circus Indonesia (OCI), which operates within Taman Safari Indonesia. The research adopts a qualitative method with a descriptive-analytical approach, based on the ongoing case study of OCI. The findings indicate that these values represent fundamental principles of Islamic work professionalism, which demand the establishment of a just and humane working system. The case of OCI reveals indications of violations of these principles, particularly in aspects such as wage justice, working conditions, and worker protection, highlighting the need to strengthen Islamic ethical values in labor practices. This study recommends the integration of Qur’anic values and decent work policies from international labor organizations into employment policies as a normative and ethical framework to guide the development of a professional and equitable work system, especially in addressing the challenges of the modern labor era.